2020
DOI: 10.3390/plants9091062
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effect of Diesel Fuel on the Seed Viability and Germination of Medicago sativa Using the Event-Time Model

Abstract: The remediation of contaminated sites using plant-based techniques has gained increasing attention in recent decades. However, information on the effects of contaminant imbibition on seed viability and germination rates are often lacking in the literature. To this end, our research investigated, by means of an event-time model, the effect of diesel fuel imbibition on the seed viability and germination rate of Medicago sativa, a plant species with great potential for remediation of organic contaminants. The eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
(41 reference statements)
1
4
0
Order By: Relevance
“…In this study, Medicago sativa L. did not exhibit any visual sign of diesel fuel toxicity. This agrees with our previous study that revealed that although diesel fuel may lead to a lag in germination, it does not significantly affect M. sativa seed viability and growth rate 18 . On the contrary, low concentrations of hydrocarbons tend to exert a stimulatory influence on M. sativa , a concept known as hormesis 15 , 31 , 32 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, Medicago sativa L. did not exhibit any visual sign of diesel fuel toxicity. This agrees with our previous study that revealed that although diesel fuel may lead to a lag in germination, it does not significantly affect M. sativa seed viability and growth rate 18 . On the contrary, low concentrations of hydrocarbons tend to exert a stimulatory influence on M. sativa , a concept known as hormesis 15 , 31 , 32 .…”
Section: Discussionsupporting
confidence: 93%
“…The triphenyltetrazolium chloride (TTC) test has been developed to provide a rapid estimate of seed viability 16 18 . TTC is a clear, water-soluble compound (a salt) which is reduced by respiring tissues to yield triphenylformazan (TPF), a water-insoluble red pigment.…”
Section: Methodsmentioning
confidence: 99%
“…Population growth, accompanied with an increasing need for energy, has led to the continuous exploration and extraction of crude oil [ 1 ]. Over the years, the increased crude oil output has had a severe unintended impact on aquatic [ 2 , 3 ] and terrestrial lives [ 4 , 5 ]. Crude oil is emitted into the environment in a variety of ways during drilling, transportation, and distribution [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Their effectiveness is limited by the depth of plant root penetration and contaminant availability [43,44], whereas the plant species used may disturb the biodiversity of the remediated area [43]. Implementation of the phytoremediation techniques on soils contaminated with DO may be hampered by other serious obstacles, i.e., the increased phytotoxicity of the soils and the detrimental effects of DO on seed viability and germination rates of remediation plants [45,46]. As a result, practical application of this remediation method becomes very difficult [46].…”
Section: Introductionmentioning
confidence: 99%
“…Implementation of the phytoremediation techniques on soils contaminated with DO may be hampered by other serious obstacles, i.e., the increased phytotoxicity of the soils and the detrimental effects of DO on seed viability and germination rates of remediation plants [45,46]. As a result, practical application of this remediation method becomes very difficult [46].…”
Section: Introductionmentioning
confidence: 99%